History of treatment of labor pains - Janowski, Jacek; Zwierzyńska, Anna; Adamczyk-Gruszka, Olga (Journal of Education, Health and Sport, 2022)
Pain is both a mental and a physical condition. It is considered by many experts to be a serious health problem or even a disease one. WHO describes it as a multidimensional phenomenon consisting of sensory, physiological, affective, spiritual and behavioral factors. Childbirth has always been associated with severe pain. The pain of childbirth has been known for centuries and is presented in every possible way as a very unpleasant sensation, not only physical but also mental. Over the years, efforts have been made to develop the best possible methods of relieving labor pain. These include non-pharmacological, such as: acupuncture, TENS or hypnosis, and pharmacological: administration of opioids and inhalation anesthetics, ending with regional analgesia techniques such as: epidural, subarachnoid anesthesia, etc. The article presents the history of the treatment of labor pain.